Enhancing the Accuracy of Solving Riccati Fractional Differential Equations - Antonela Toma; Flavius Dragoi; Octavian Postavaru (Fractal and Fractional, 2022)
In this paper, we solve Riccati equations by using the fractional-order hybrid function of block-pulse functions and Bernoulli polynomials (FOHBPB), obtained by replacing x with <semantics>xα</semantics>, with positive <semantics>α</semantics>. Fractional derivatives are in the Caputo sense. With the help of incomplete beta functions, we are able to build exactly the Riemann–Liouville fractional integral operator associated with FOHBPB. This operator, together with the Newton–Cotes collocation method, allows the reduction of fractional differential equations to a system of algebraic equations, which can be solved by Newton’s iterative method. The simplicity of the method recommends it for applications in engineering and nature. The accuracy of this method is illustrated by five examples, and there are situations in which we obtain accuracy eleven orders of magnitude higher than if <semantics>α=1</semantics>.